1481 Evaluation of the efficacy of risk management strategies in the protection of healthcare workers handling cytotoxic drugs. (24th April 2018) - Kelly, S; Reid, A
Abstract : Introduction: Cytotoxic drugs are used as part of cancer chemotherapy regimens in the healthcare setting and are recognised occupational hazards. Acceptable levels of exposure have not been established therefore national guidelines advocate levels as low as reasonably possible. This aim of this study was to establish whether training and reminders regarding work practices would limit occupational exposure to cytotoxic drugs. Platinum was chosen as the index cytotoxic drug due to its frequent use and validated analysis methods. Initial studies performed in 2007 and 2012 in our instituion found that focused training on the appropriate handling of cytotoxic agents brought about a reduction in occupational exposure to the drug. Methods: A prospective study was carried out in the oncology day ward and pharmacy aseptic compounding unit of a tertiary level hospital. Urinalysis for urinary platinum was carried out on 10 staff members, including one control. End of shift, end of week samples were collected from a randomly selected group of staff. Samples were sent to an internationally accredited laboratory for analysis. A review of work processes was also performed. Result: The mean urinary platinum level was 26.19 nmol/mol creatinine (range 15.89–91.42 nmol/mol creatinine), which is well above the reference level for the unexposed worker of 10 nmol/mol. The control was also high at 49.71 nmol/mol. Mean platinum concentration values increased by a factor of 11 from the 2012 study. Discussion: These high urinary platinum results were unexpected. There had been no changes in equipment or work practices since the last study performed in 2012. As the control result was also high this was most likely a laboratory error or contamination rather than true high occupational exposures. To further evaluate this, we repeated testing and these results are pending (expected end of July).